Characterization of Acid-Aluminium Sensitive Mutants of Soybean Symbiont Bradyrhizobium japonicum Generated by Transposon Mutagenesis - ARIS TRI WAHYUDI; ANDINI PURNAWIJAYA; DINI NURDIANI; TEDJA IMAS (Microbiology Indonesia, 2007)
Acid-aluminium sensitive mutants of symbiotic bacterium Bradyrhizobium japonicum BJ11 (designated as AAS11) and KDR15 (designated as AAS15) were constructed by mini-Tn5 transposon mutagenesis to study genes involved in acid-aluminium tolerance (AAT) in B. japonicum. Transposon delivery was carried out through conjugation between B. japonicum strains as recipients and Escherichia coli S17-1 (ë pir) carrying pUTmini- Tn5Km1 as a donor strain. The result showed that frequency of transconjugation was in the range of 6.7 x 10-7 to 7.1 x 10-6 cell per recipients. AAS11 and AAS15 mutants did not grow on Ayanaba media (pH 4.5) containing 50 μM Aluminium. These mutants remained able to form root nodules of Siratro (Macroptilium arthropurpureum) plants revealing genes interrupted by transposon which were responsible for acid-Al tolerance did not correlate with the nodulation genes. Strains tolerant to acid-aluminium and their mutants with a wild type sensitive to acidaluminium were characterized by accumulating phosphate and aluminium absorption. Compared to the wild type acid-aluminium tolerant B. japonicum, there was approximately a three- to eight-times decrease in phosphate accumulation and a five- to seven-times increase in aluminium absorption by these mutants. These results suggest that aluminium and phosphate contents in the bacterial cells may be involved in mechanisms of acid-Al tolerance of B. japonicum grown in acid-aluminium stress conditions.